Code-Switching and Code-Mixing in the Film Assal Eswed: A Sociolinguistic Study - Haq, Iman Amirul; Dayudin; Djaliel, Maman Abdul (Mantiqu Tayr: Journal of Arabic Language, 2026)
This study investigates bilingual practices in contemporary Arab society by examining code-switching and code-mixing in the film Assal Eswed, directed by Khalid Marei. The study aims to identify the types and linguistic forms of code-switching and code-mixing, as well as the sociolinguistic factors influencing their occurrence. Employing a descriptive-analytical method within a sociolinguistic framework, the data consist of characters’ utterances collected through observation, transcription, and classification. The analysis is based on the theories of code-switching and code-mixing proposed by Suwito and Chaer, the code-switching factors outlined by Hoffmann and Saville-Troike, and the code-mixing factors proposed by Suwito and Suwandi. The findings reveal that all instances of code-switching are external, predominantly involving shifts from Arabic to English, while code-mixing occurs in the form of words, phrases, and clauses. The influencing factors include role identification, register adjustment, explanatory needs, shared mother tongue, lexical gaps, and habitual speech patterns. These findings indicate that Assal Eswed reflects the interaction between language, identity, and globalization in a bilingual Egyptian context, highlighting film as a relevant medium for sociolinguistic analysis and contributing a foundation for broader investigations of language contact, identity, and bilingualism in Arabic media.